Characterization of a double-sided Si(Li) strip Compton polarimeter. (29th January 2015) - Blumenhagen, K-H; Gumberidze, A; Märtin, R; Schell, N; Spillmann, U; Weber, G; Stöhlker, Th
Abstract: The response of a double-sided segmented Si(Li) detector system has been investigated. The detector has been irradiated with a collimated, highly linearly polarized beam of 53.2 keV photons from the synchrotron radiation source PETRA III at DESY. The detector was mounted on a platform that could be moved with μm precision thus allowing for a defined beam position on the detector surface. In this paper, the effects of the isolation gaps (gap width = 50 μm) between adjacent segments (strips) were studied, in particular with respect to the effect of charge sharing. The fraction of such charge sharing events increases from about 5% (beam hits center of a strip) to over 50% when the beam is focused just on a gap. The fraction of reconstructed Compton scattering events, which is interesting for Compton polarimetry, amounts to about 3% with the beam impinging at a strip center and 2.8% on average. It can therefore be concluded that events related to charge sharing do not critically degrade the performance of the detector as a Compton polarimter.